PEDAGOGICAL DISCOURSE RESOURCES AND INCENTIVES IN THE MODERN UKRAINIAN SOCIETY - Syladii, Ivan (Mountain School of Ukrainian Carpaty, 2018)
In the article, the resources and stimuli of the pedagogical discourse in modern Ukrainian society are analyzed; its role in view of the implementation by the education system of the general purpose to attract people to the achievements of culture, knowledge system, the process of forming competences. According to the author's definition, education is, first of all, the process of disseminating scientific knowledge among those who are studying, their mastering a system of scientific concepts and spiritual values that reproduces the picture of nature, society and thinking. All of them are far from unambiguous, and therefore require interpretation, discourse. The main resource of the pedagogical discourse is innovative pedagogical activity as a special kind of creative activity aimed at updating the education system. In the framework of the pedagogical discourse, at the same time, a scientific and an educational discourses function, therefore a scientific discourse should become a powerful resource of the pedagogical discourse. Thus, in the field of educational communication, the pedagogical discourse is an integrated entity that combines the components of scientific and educational discourse. A characteristic feature of the present stage of the development of the pedagogical discourse is search for a new interdisciplinary multicultural dialogue. The pedagogical discourse is where interactions between a teacher and a student occur and where cognition is carried out. A discourse is a typical social event that involves the interaction of communication participants through verbal texts and other sign complexes in a particular situation and in certain socio-cultural conditions of communication. The resource core and the fundamental essential characteristic of the pedagogical discourse is intellectual interaction of the basic pair of communication participants - a teacher and a student, each of whom carries out his intellectual activity. Interaction is a type of direct or indirect, external or internal relations, relation ships. The intellectual interaction of the teacher and the student in the pedagogical discourse involves the mutual mental influence of the subjects of the educational process on each other in their common activity and interpersonal relations that leads to a change in the intellectual state of one or both subjects. The pedagogical discourse in the structure of innovative processes in the education system is at the same time a unit of study, and a communicative model of verbal activity of the participants in the educational situation. This activity receives verbal performance as a system of ideas, values and interests. A discourse can be considered a perfect form of communication. Consequently, all resources and incentives for the functioning of the pedagogical discourse available in the society should contribute to the development of the interaction of its main actors.